IMPROVING THE STUDENTS’ ENGLISH PROFICIENCY THROUGH LITERATURE: LANGUAGE-BASED APPROACH - R Bunga Febriani; Dwi Rukmini; Ahmad Sofwan; Issy Yuliasri (JALL (Journal of Applied Linguistics and Literacy), 2018)
This article presents a library study of an approach of teaching literature that emphasizes on improving the students’ English language proficiency through literature and a practice of the approach in the classroom by using a literary work written by Anton Chekhov entitled ‘A Marriage Proposal’. The study aims at discussing   a theory of an approach for teaching literature which attempts to improve the students’ linguistic competence through literary works. The approach is chosen in accordance to Van (2009)’s review of the approaches to literary analysis, in this case by emphasizing on the approach for improving the students’ language skill through literature which is called Language-based Approach. This study also apply Lazar’s (1993) procedures of language-based approach which cover the pre-reading, while-reading, and post-reading activities.    Keywords: Language-Based technique, , literary works.